Universal IR holography, scalar fluctuations, and glueball spectra - Anabalón, Andrés [UNESP]; Nastase, Horatiu [UNESP] (American Physical Society (APS), 2024)
We show that the d'Alembertian operator with a possible mass term in the anti-de Sitter (AdS) soliton and more general confining gravity dual backgrounds admits infinitely many different spectra. These can be interpreted as different theories in the infrared and correspond to multitrace deformations of either the Dirichlet or the Neumann theory. We prove that all these fluctuations are normalizable and provide examples of their spectra. Therefore, the AdS soliton can be interpreted as giving a holographic Renormalization Group flow between a universal UV theory at the AdS boundary and these infinitely many possibilities in the IR, obtained by deformations. The massive spectrum of the double trace deformation in AdS5 allows the matching of the large-N glueball masses of lattice QCD3; the ratio of the ground states of the 2++ and 0++ channels are in full agreement with the lattice prediction. When considering AdS7 and the four-dimensional pure glue theory, a remarkably general picture emerges, where we can write formulas for the fluctuations that are in agreement with ones from holographic high-energy scattering and from AdS/CFT with IR and UV cutoff. We point out that this log branch in the IR in D dimensions can be seen as the usual logarithmic branch of scalar fields saturating the Breitenlohner-Freedman bound in a conformally rescaled metric, with AdSD-1×S1 asymptotics.